Disruptive technologies in health care disenchanted: a systematic review of concepts and examples. (16th May 2022) - Perleth, Matthias; Di Bidino, Rossella; Huang, Li-Ying; Jones, Lydia; Mujoomdar, Michelle; Myles, Susan; Pichon-Riviere, Andres; Sabirin, Junainah; Schuller, Tara; Washington, Jennifer
Abstract: Objectives: To clarify the concept of disruptive technologies in health care, provide examples and consider implications of potentially disruptive technologies for health technology assessment (HTA). Methods: We conducted a systematic review of conceptual and empirical papers on healthcare technologies that are described as " disruptive. " We searched MEDLINE and Embase from 2013 to April 2019 (updated in December 2021). Data extraction was done in duplicate by pairs of reviewers utilizing a data extraction form. A qualitative data analysis was undertaken based on an analytic framework for analysis of the concept and examples. Key arguments and a number of potential predictors of disruptive technologies were derived and implications for HTA organizations were discussed. Results: Of 4, 107 records, 28 were included in the review. Most of the papers included conceptual discussions and business models for disruptive technologies; only few papers presented empirical evidence. The majority of the evidence is related to the US healthcare system. Key arguments for describing a technology as disruptive include improvement of outcomes for patients, improved access to health care, reduction of costs and better affordability, shift in responsibilities between providers, and change in the organization of health care. A number of possible predictors for disruption were identified to distinguish these from " sustaining " innovations. Conclusions: Since truly disruptive technologies could radically change technology uptake and may modify provision of care patterns or treatment paths, they require a thorough evaluation of the consequences of using these technologies, including economic and organizational impact assessment and careful monitoring.